Clinical Outcomes of Drug-Coated Balloon in Coronary Patients with and without Diabetes Mellitus: A Multicenter, Propensity Score Study. (29th July 2021) - Pan, Liang; Lu, Wenjie; Han, Zhanying; Pan, Sancong; Wang, Xi; Shan, Yingguang; Wang, Xule; Zheng, Xiaolin; Li, Ran; Zhou, Yanjun; Qin, Peng; Shi, Qiangwei; et al.
Abstract : Background . Relative to nondiabetic patients, percutaneous coronary intervention (PCI) in patients with diabetes mellitus (DM) is associated with inferior clinical outcomes. We aimed to evaluate the outcomes of drug-coated balloon (DCB) in diabetic versus nondiabetic patients. Methods and Results . In this observational, prospective, multicenter study, we compared the outcomes of patients with and without DM after undergoing PCI with DCBs. Target lesion failure (TLF) was analyzed as primary endpoint. Secondary endpoints were the rates of target lesion revascularization (TLR), major adverse cardiovascular events (MACE), cardiac death, myocardial infarction (MI), and any revascularization. Propensity score matching was used to assemble a cohort of patients with similar baseline characteristics. Among 2, 306 eligible patients, 578 with DM and 578 without DM had similar propensity scores and were included in the analyses. During follow-up (366 ± 46 days), compared with DM patients, patients without DM were associated with a lower yearly incidence of TLF (2.77% vs. 5.36%; OR, 1.991; 95% CI, 1.077 to 3.681; P = 0.025 ) and TLR (1.90% vs. 4.15%; OR, 2.233; 95% CI, 1.083 to 4.602; P = 0.026 ). No significant differences were observed with regards to rates of MACE (OR: 1.580, 95% CI: 0.912-2.735; P = 0.100 ), cardiac death (OR: 1.608, 95% CI: 0.523-4.946; P = 0.403 ), MI (OR: 4.042, 95% CI: 0.855-19.117; P = 0.057 ), and any revascularization (OR: 1.534, 95% CI: 0.983-2.393; P = 0.058 ). Conclusions . Diabetic patients experience higher TLF and TLR rates following DCB angioplasty without substantial increase in the risk of MACE, cardiac death, MI, or revascularization.